XitoSBML: A Modeling Tool for Creating Spatial Systems Biology Markup Language Models From Microscopic Images - Ii, Kaito; Mashimo, Kota; Ozeki, Mitsunori; Yamada, Takahiro G.; Hiroi, Noriko; Funahashi, Akira (Frontiers in Genetics, 2019)
XitoSBML is a software tool designed to create an SBML (Systems Biology Markup Language) Level 3 Version 1 document from microscopic cellular images. It is implemented as an ImageJ plug-in and is designed to create spatial models that reflect the three-dimensional cellular geometry. With XitoSBML, users can perform spatial model simulations based on realistic cellular geometry by using SBML-supported software tools, including simulators such as Virtual Cell and Spatial Simulator. XitoSBML is open-source and is available at https://github.com/spatialsimulator/XitoSBML/. XitoSBML is confirmed to run on most 32/64-bit operating systems: Windows, MacOS, and Linux.